FREQUENCY OF BALANITIS XEROTICA OBLITERANS AMONG BOYS WITH PHIMOSIS - Vujić, Nemanja; Viduljević, Mihajlo; Bižić, Marta (Medicinski podmladak, 2018)
Introduction: Balanitis xerotica obliterans (BXO) is an inflammatory disease of unknown etiology and pathogenesis, that represents genital form of lichen sclerosus. Disease is located on foreskin, glans of penis and on urethra. It was discovered that BXO is common cause of phimosis. There is evidence of connections between balanitis xerotica obliterans and appearance of squamous cell carcinoma. The diagnosis of the disease can be clinical and pathohistological. Therapy can be conservative and surgical.The Aim: Determining the frequency of BXO among the boys with phimosis in the light of increasing number of evidence about importance of this clinical entity in development of many complications of urogenital system.Material and methods: Our research contained 470 male patients aged from 1 to 18 years. All the patients who were included in the study were surgically treated in period from 1. January 2014. till 1. January 2017. in University Children’s Hospital and all of them had diagnosed phimosis. All the patients underwent circumcision. Foreskins that were suspicious of BXO diagnosis, but could not be diagnosed clinically, were sent to pathohistological analysis. Statistical methods used for measuring central tendency and for determining frequency of BXO were methods of descriptive statistics, or frequency analysis in IBM SPSS Statistics 22 program.Results: Patients with phimosis were in average age of 9.12 ± 4.46 (1-18) years. After data analysis, it was established that in the group of 470 patients there are 48 with BXO diagnosis (10.21%). Patients with BXO were in average age of 10.33 ± 3.14 (6-18) years.Conclusion: Our research has shown that the frequency of BXO among boys with phimosis population is coherent with results of other studies. We concluded that pathohistological analisys of the foreskin is necessary to avoid false negative results after clinical examination.Keywords: balanitis xerotica obliterans, lichen sclerosus, phimosis